2021
DOI: 10.3390/ma14040924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soft X-ray Irradiation on Film Properties of a Hydrogenated Si-Containing DLC Film

Abstract: The effect of soft X-ray irradiation on hydrogenated silicon-containing diamond-like carbon (Si-DLC) films intended for outer space applications was investigated by using synchrotron radiation (SR). We found that the reduction in film thickness was about 60 nm after 1600 mA·h SR exposure, whereas there was little change in their elemental composition. The reduction in volume was attributable to photoetching caused by SR, unlike the desorption of hydrogen in the case of exposure of hydrogenated DLC (H-DLC) film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For example, although soft X-rays influence the whole F-DLC film instead of just the outermost surface, a low F content contributes to resisting soft X-ray irradiation [104,105]. Similarly, the presence of Si doping could restrict the desorption of hydrogen by X-ray irradiation [106,107]. Also, Liu et al [108][109][110] found that the liquid/DLC composite coating showed radiation resistance depending on its composition and structure.…”
Section: Properties In Space Radiationmentioning
confidence: 99%
“…For example, although soft X-rays influence the whole F-DLC film instead of just the outermost surface, a low F content contributes to resisting soft X-ray irradiation [104,105]. Similarly, the presence of Si doping could restrict the desorption of hydrogen by X-ray irradiation [106,107]. Also, Liu et al [108][109][110] found that the liquid/DLC composite coating showed radiation resistance depending on its composition and structure.…”
Section: Properties In Space Radiationmentioning
confidence: 99%